A rare encounter of obstructed direct inguinal hernia - Singh, Amit Kumar; Rajbhandari, Nripesh; Malla, Balaram; Bhatta, Gakul (Journal of Society of Surgeons of Nepal, 2019)
The direct inguinal hernia has a wider neck and thus usually doesn’t present as strangulation or incarceration in comparison to the indirect component. When direct inguinal hernias are untreated for a longer duration, they may get strangulated and incarcerated. Hence such long-standing direct hernias with features of intestinal obstruction and /or peritonism should be promptly seen and diagnosed to prevent massive and unwanted intestinal resection. We are reporting a case of 83-year-old male presented to Surgical Emergency Department of Dhulikhel Hospital, Kathmandu University hospital with complaints of swelling in the right inguinoscrotal region for 12 years and progressed to become irreducible and painful for 12 hours. Clinically he had an acute intestinal obstruction. Intra-operatively we found a direct hernia containing congested small bowel loops and toxic fluids. The toxic fluid was suctioned and after confirming viability, modified Bassini’s repair was done with reinforcement of the posterior wall. Even direct inguinal hernia of longer duration can cause acute or sub-acute intestinal obstruction with or without features of peritonism. This complication is more common in elderly patients.